Estudo sobre os determinantes do investimento na indústria de transformação brasileira: análise setorial para o período de 1996 a 2012 - Nunes, Stephano Hertal Farias [UNESP] (Universidade Estadual Paulista (Unesp), 2015)
Brazil experienced an industrialization process that aimed to replace imported products for goods produced domestically. This fact, which occurred deliberately by the state over three decades (1950-1970), named industrialization by import substitution (IIS). Industrialization ensued gradually: first the installation of the industrial park of consumer goods, durable consumer goods and subsequently the installation of capital and intermediate goods industry. No relative stability for the construction of minimally reliable expectations about the future, the 1980s, known as the lost decade, is seen as a period of slowing economic activity and falling investment. The succession of economic plans implemented in order to curb inflation only succeeded with the plan Real, in 1994. Mainly from this year investment rates in Brazil has remained below 20% of gdp, one of the reasons given for the weak economic growth. The objective of this work is to build a model that describes the impact of economic variables on the decision to invest in new and stable period of the brazilian economy. This research is part of a small, but growing number of studies dedicated to understanding the manufacturing sector in the optical industry, highlighting the heterogeneity created throughout the history of industrialization process. Through a long process of conversion of data, it was possible to work with statistics PIA (IBGE) from 1996 to 2012 (last year released until the preparation of the work). The research is organized into sections theoretical character, historical and empirical. The first section is in charge of presenting the main theories about the determinants of investment. The second section will present Brazil's industrialization process and the evolution of economic variables and sector investment in the manufacturing industry. In the third and final section are estimated empirical models to examine the ...

O Brasil passou por um processo de industrialização que visava substituir os produtos importados por mercadorias produzidas internamente. Esse fato, que ocorreu de forma deliberada pelo Estado ao longo de três décadas (de 1950 a 1970), recebeu o nome de Industrialização por Substituição de Importações (ISI). A industrialização se sucedeu de forma gradativa: primeiro a instalação do parque industrial dos bens de consumo leves, bens de consumo duráveis e, posteriormente, a instalação da indústria de bens de capital e intermediários. Sem a relativa estabilidade para construção de expectativas minimamente confiáveis quanto ao futuro, a década de 1980, conhecida como década perdida, é tida como um período de desaceleração da atividade econômica e queda dos investimentos. A sucessão de planos econômicos implantados a fim de conter a inflação só obteve sucesso com o plano Real, em 1994. Principalmente a partir desse ano as taxas de investimento no Brasil tem se mantido abaixo de 20% do PIB, um dos motivos apontados para o fraco crescimento da economia. O objetivo deste trabalho é construir um modelo que descreva o impacto de variáveis econômicas sobre a decisão de investir no período recente e estável da economia brasileira. Esta pesquisa faz parte de um pequeno, mas crescente grupo de estudos que se dedicam a compreender a indústria de transformação sob a ótica setorial, destacando-se as heterogeneidades criadas ao longo da industrialização. Um longo processo de conversão dos dados permitiu trabalhar com estatísticas da PIA (IBGE) de 1996 a 2012 minimizando o impacto da mudança de metodologia em 2007. A pesquisa está organizada em seções de caráter teórico, histórico e empírico. A primeira seção se encarrega de apresentar as principais teorias sobre os determinantes dos investimentos. A segunda seção apresentará o processo de industrialização do...
Keywords: Economia; Investimentos; Industria Aspectos econômicos; Industria de transformação - Brasil; Economic